A large deletion in the Plasminogen gene is associated with ligneous membranitis in a Maltese dog. (9th August 2021) - Turba, M. E.; Ostan, P. C.; Ghetti, S.; Dajbychova, M.; Dondi, F.; Gentilini, F.
Summary: Ligneous membranitis/conjunctivitis (LM, OMIM 217090) is a hereditary disorder caused by a congenital plasminogen (PLG) deficiency. In veterinary medicine, LM (OMIA 002020‐9615) has rarely been reported in Golden Retrievers, Yorkshire Terriers, Doberman Pinschers and Scottish Terriers. In the latter breed, an A>T variation in an intron donor site of the PLG gene (PLG, c.1256+2T>A) has been found to be the sole causative molecular defect reported to date in dogs. Owing to the absence of plasmin enzymatic clearance which in turn depends on the lack of its proenzyme plasminogen, fibrin deposits tend to accumulate in viscous membranes on the eyes, triggering and sustaining an intense inflammatory response. A case of LM was diagnosed in a 7‐month‐old male Maltese dog. The dog was examined for severe recurrent conjunctivitis. A diagnosis of ligneous conjunctivitis was made by an ophthalmologist after a thorough eye examination and was confirmed by a complete lack of plasma activity of plasminogen. The main local signs were redness of the conjunctiva with persistent membranes having ligneous (wood‐like) membranes on the eyes. The disease was associated with a complex rearrangement involving the plasminogen gene loci, causing the complete deletion of exon 1. This study provides a spontaneous animal model for LM associated with complete plasminogen deficiency and provides a method for detecting affected or carrier dogs.